2012
DOI: 10.5772/2619
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Application of Microwave Heating

Abstract: China, works intensively in two research fields supported by China national research projects. First, he is interested in developing practical, cheap and environmentally friendly methods to synthesize ceramic powders at low cost, including the preparation of SiC powders and whiskers by microwave heating, through which the synthesis temperature and reaction time have been decreased significantly. Secondly, he is focused on the preparation and application of semiconductor photocatalyst. Large scale production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 95 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Alcohols and organic acids, for example, are produced via oxidative lipid degradation. The Maillard process produces pyrrole, pyrazine, and sulfur compounds ( 107 ). Microwave, on the other hand, changes the structure of proteins and increases the number of binding sites that react with volatile chemicals, boosting taste adsorption ( 1 , 108 ).…”
Section: The Influence Of Microwave On Flavor Nutrients and Securitymentioning
confidence: 99%
“…Alcohols and organic acids, for example, are produced via oxidative lipid degradation. The Maillard process produces pyrrole, pyrazine, and sulfur compounds ( 107 ). Microwave, on the other hand, changes the structure of proteins and increases the number of binding sites that react with volatile chemicals, boosting taste adsorption ( 1 , 108 ).…”
Section: The Influence Of Microwave On Flavor Nutrients and Securitymentioning
confidence: 99%
“…The heating based on the interaction between the microwaves and the material presents specific advantages [1]: the heating is volumetric and it is initiated in the core of the material; the thermal flux is from the core to the surface of the piece; the heating time is generally lower comparing to the classic heating processes and better energy efficiency is recorded; improvement of the product quality by non-affecting of the local chemical composition such in the case of the classical thermal sources as flame or electric arc or laser beam. The application of the microwaves, as thermal source, registers large number of technological processes as heat treatment, sintering, defrosting, de-polymerization, mineral processing or degeneration of structures [2][3][4][5][6][7]. Several authors reported research on the welding of different materials by using microwave heating [7][8][9][10] and starting with that the behavior of the materials during welding is important to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Because PE is one of the most used polymers in domestic and technical application [11][12][13][14], the influence of the microwave heating on the characteristics of the HDPE80 and HDPE100 was analyzed within the present paper. The principle of the microwave heating consists in the development of some friction processes because the continuous orientation of the polar particles, inside the materials, after the electric lines field [1,3,5]. The heat is generated because of the conversion of the kinetic energy in thermal energy which is a specific phenomenon of the friction process and because of the ionic conduction because of the movement of the free charges, under the magnetic field action, and because their collision with the particles with the null charge [1,3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation